Relação entre gastos e ações da vigilância sanitária nos municípios dos Ceará - Fraga, Antonio Carlos Araújo (2018)
Based on the interpretation of the Constitution and the Organic Health Law (Law No. 8,080 / 90), it is understood that the municipality is given the authority to carry out the Health Surveillance actions (VISA). The execution of these actions requires organization, as well as human, physical and financial resources for the performance of activities aimed at controlling health risks. In this sense, the present study aims to analyze the relationship between VISA expenditures and actions in the municipalities of Ceara, from 2013 to 2017. This is an ecological study, with a quantitative character and a descriptive approach, using secondary data public domain information systems and unrestricted access to the 184 municipalities that make up the state of Ceara, in which the evolution of the selected variables was verified in the period from 2013 to 2017. In relation to public expenditure with the Health Surveillance Sub-results point to an increase in the amounts spent with VISA in the municipalities of Cearaeach year, highlighting a decrease in the values for 2017, presented by about 70% of the municipalities of the state of Ceara. There was an increase in the annual average of VISA expenditures, which increases the population size of the municipalities. Regarding the per capita VISA expenditures within each population extract, the smaller municipalities had the highest expenditures per capita with VISA and municipalities with up to 10,000 inhabitants presented per capita expenditure figures like those recorded by the most populous municipality. Regarding the actions of VISA carried out by the municipalities of Ceara, it was verified that of the seven actions accompanied by Indicator 41, the municipalities present a better level of implementation of the action of Sanitary Inspection. However, many municipalities in the state, still do not carry out the procedure of Establishment of Administrative Sanitary Procedures. Even if the data cannot evaluate the quality of the action or of the registration made, the identified increments point to a better and better organization of the Health Surveillance services in the municipalities of the state of Ceara. Given the limitations imposed by the available data, it was not possible to establish a numerical relationship between VISA expenditures and actions in the municipalities. Finally, we consider that the results of this study may constitute a baseline for monitoring the allocation of resources in VISA, as well as for a discussion on financing and execution of VISA actions, considering the needs and specificities of each municipality.